PERANAN KELOMPOK TANI DALAM MENINGKATKAN PRODUKSI PADI SAWAH DI KELURAHAN NANGA BARAS KECAMATAN SAMBI RAMPAS KABUPATEN MANGGARAI TIMUR - Anjalin, Anastasia Lastika; Nikolaus, Serman; Nendissa, Doppy Roy (Buletin Ilmiah Impas, 2023)
Objectives of this study were: (1) to determine the role of farmer group in increasing the rice production of Nanga Baras Village, Sambi Rampas District, East Manggarai Regency and (2) to identify problems faced by the farmer group in Nanga Baras Village, Sambi Rampas District, East Manggarai Regency. To get data in this study it was used a survey method. To answer the first objective, data were analyzed by the application of such descriptive statistics as: Mean Score, and Percentage Value, while to answer the second objective, the data were analyzed by the application of qualitative approach, that was, recording all factors that inhibited the increase of rice production. Results of analysis demonstrated that: (1) the production of rice after farmers become the member of farmer group was increase; (2) the role of farmer group in increasing the rice production was in “quite good category" because the average score obtained was only 2.13 and the percentage value of this score in achieving the maximum score was 53.25%.; and (3) problems faced by farmers in increasing the rice production were capital and climate.